2014
DOI: 10.1063/1.4879875
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gridded gate structure on gas sensing behavior of hydrogen

Abstract: A gridded Pt/SiO2/Si MOS sensor for hydrogen detection has been fabricated on p-type ⟨100⟩ Si wafer having resistivity (1–6 Ω cm). The SiO2 and Platinum (Pt) gate thickness were kept about 10 nm and 35 nm. The performance of Pt gate MOS sensor was evaluated through C-V characteristics (capacitance vs voltage) upon exposure to H2 (250 ppm–4000ppm) at different frequencies (25 kHz and 50 kHz) in a closed chamber at air ambient atmosphere. The capacitance of the sensor decreases with increase in frequency as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Cumulatively with this effect, charged states presented at the metal-oxide interface were also passivated, creating a dipole layer between Pd and SiO 2 . However, it was shown that the main contributor to hydrogen sensitivity was given by the further diffusion of H + deeper into the oxide and interaction with SiO 2 bulk traps [22,[38][39][40]. The trade-offs for this increase in susceptibility to H 2 were that the structure took a longer time to both stabilize its response and to release stored hydrogen atoms as the environment becomes inert.…”
Section: Hydrogen Detection Principlementioning
confidence: 99%
“…Cumulatively with this effect, charged states presented at the metal-oxide interface were also passivated, creating a dipole layer between Pd and SiO 2 . However, it was shown that the main contributor to hydrogen sensitivity was given by the further diffusion of H + deeper into the oxide and interaction with SiO 2 bulk traps [22,[38][39][40]. The trade-offs for this increase in susceptibility to H 2 were that the structure took a longer time to both stabilize its response and to release stored hydrogen atoms as the environment becomes inert.…”
Section: Hydrogen Detection Principlementioning
confidence: 99%
“…This is due to the relative simplicity of the fabrication process, together with their high sensitivity and signal amplification capability. Starting from the standard capacitor structure: catalytic metal gate-silicon dioxide-silicon carbide (MOSiC) [10], the technological processes were continually adjusted for better-quality structures, notable progress in sensing qualities being reported [11][12][13]. Despite their well-known drawbacks, the most used catalytic gate metal remains Pd [8] and Pt [14], while the most research effort is concentrated on the improving the oxide characteristics.…”
Section: Introductionmentioning
confidence: 98%